Churg-Strauss Syndrome following PTU Treatment - Quax, R. A. M. (Hindawi Publishing Corporation, 2009)
Propylthiouracil (PTU) is a frequently prescribed drug in the treatment of hyperthyroidism. The use of PTU is, however, accompanied by numerous potentially serious side effects including vasculitis. PTU-related vasculitides can present as haematuria, pulmonary haemorrhage, or cutaneous lesion together with aspecific symptoms such as fever, myalgia, arthralgia, and fatigue. Cerebral involvement is seldom observed. We present a 49-year-old female with Graves' disease and asthma, who developed paresis of the proximal extremities, eosinophilia, pulmonary, and cutaneous lesions following treatment with PTU. A cerebral vasculitis consistent with Churg-Strauss syndrome (CSS) was suspected. Although cerebral involvement is seldom observed with PTU treatment, cerebral vasculitis should be considered in patients developing CNS symptoms.